Trans-Amazonian U-Th-Pb monazite ages and P-T-d exhumation paths of garnet-bearing leucogranite and migmatitic country rock of the southeastern Tandilia belt, Rio de la Plata craton in Argentina - Martinez, Juan Cruz (2017)
A garnet-bearing leucogranite and two country rocks from the Transamazonian Tandilia belt of the Rio de la Plata craton were studied in detail. The leucogranite contains garnet with homogeneous composition of pyr6(gros + andr)2spes5alm87. In a garnet-biotite migmatite, the core and rim compositions of garnet are pyr1.7(gros + andr)5spes5.6alm87.7 and pyr1.2(gros + andr)5.5spes6.7alm86.6, respectively. These compositions in a sillimanite-garnet-muscovite migmatite are pyr4(gros + andr)2.7spes2.7alm90.6 and pyr2.7(gros + andr)4spes3.2alm90.1, respectively. We used this information to decipher the P-T evolution of the rocks applying P-T and T-H2O pseudosections with the PERPLE_X computer software package taking into consideration deformational microstructures. The leucogranite records an isothermal decompression from 5.3 to 3.8 kbar at 665 °C. The garnet-biotite migmatite was exhumed from 5.5 kbar at 630 °C to 4.3 kbar at 615 °C and the sillimanite-garnet-muscovite migmatite from supersolidus conditions of 670 °C and 3.6 kbar to 625 °C at 2.4 kbar. Late andalusite formed in this rock. Seventy four analyses of 28 monazite grains of the country rocks yielded three groups of U-Th-Pb ages which were related to a collisional event (I: ca. 2.13–2.14 Ga.), a postcollisional thermal overprint (II: ca. 2.01 Ga) and slow cooling of the orogen (III: 1.80–1.90 Ga). Inherited ages of 2.28 and 2.25 Ga could refer to an early accretionary stage of the orogen. An age of 2.41 Ga indicates the presence of recycled Siderian continental crust. Synkinematic crystallization of melts and the subsolidus development of an S2-foliation, demonstrated by deformational microstructures, occurred during the exhumation of the studied area from depths of ~ 18 km to ~ 8 km in the time interval 2.01–1.90 Ga.